Rural Community Development Click-by-Click. Processes and dynamics of digitally supported social innovations in peripheral rural areas - Zerrer, Nicole; Sept, Ariane; Christmann, Gabriela (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
Even before the Covid-19 pandemic, residents in peripheral and structurally weak rural areas began to move into the digital age. Digital tools are being used and developed to address existing challenges in rural areas such as local communication, healthcare or mobility. Against the background of a conceptual framework of social and digital innovations from a process perspective, this paper asks how the processes and dynamics of digitally supported social innovations in rural areas can be understood and described. By analysing five villages in Germany, we show that the digital initiatives – despite their different contexts, contents and driving actors – develop over three phases: an inspiration phase, an emergence phase and a consolidation phase. This dynamic process can be interpreted as “linear-circular”, because while overall a very targeted development of innovative problem solutions can be observed within the three-phase process, at the same time creative development loops and new inspirations exercise influence.